2023
DOI: 10.3389/fpls.2023.1214602
|View full text |Cite
|
Sign up to set email alerts
|

Class I and II NADPH-cytochrome P450 reductases exhibit different roles in triterpenoid biosynthesis in Lotus japonicus

Abstract: Cytochrome P450 monooxygenases (CYPs) are enzymes that play critical roles in the structural diversification of triterpenoids. To perform site-specific oxidations of the triterpene scaffold, CYPs require electrons transferred by NADPH-cytochrome P450 reductase (CPR), which is classified into two main classes, class I and class II, based on their structural difference. Lotus japonicus is a triterpenoids-producing model legume with one CPR class I gene (LjCPR1) and a minimum of two CPR class II genes (LjCPR2-1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…SelFdx1499/SelFdR0978 has a higher electron transfer efficiency when interacting with P450 monooxygenase PikC, and their catalytic efficiency for YC-17 was the highest, reaching 99.1%. Istiandari et al [ 62 ] found that mutation of the CRP gene LjCPR1 in Lotus japonicus had no effect on product yield, while deletion of the CRP gene LjCPR2-1 significantly reduced soybean saponin precursor yield. When constructing the P450s catalytic system, it is necessary to consider not only their species in addition to, their expression quantity.…”
Section: Electron Transfer Pathway Engineeringmentioning
confidence: 99%
“…SelFdx1499/SelFdR0978 has a higher electron transfer efficiency when interacting with P450 monooxygenase PikC, and their catalytic efficiency for YC-17 was the highest, reaching 99.1%. Istiandari et al [ 62 ] found that mutation of the CRP gene LjCPR1 in Lotus japonicus had no effect on product yield, while deletion of the CRP gene LjCPR2-1 significantly reduced soybean saponin precursor yield. When constructing the P450s catalytic system, it is necessary to consider not only their species in addition to, their expression quantity.…”
Section: Electron Transfer Pathway Engineeringmentioning
confidence: 99%